2021
DOI: 10.3390/nu13103471
|View full text |Cite
|
Sign up to set email alerts
|

Oleanolic Acid-Enriched Olive Oil Alleviates the Interleukin-6 Overproduction Induced by Postprandial Triglyceride-Rich Lipoproteins in THP-1 Macrophages

Abstract: Oleanolic acid (OA), a triterpene that is highly present in olive leaves, has been proposed as a component of functional foods for the prevention of metabolic syndrome, due to its anti-inflammatory activity. We analyzed the effects of OA on inflammatory parameters and signaling proteins in LPS-stimulated THP-1 macrophages. Thus, THP-1 macrophages were incubated with LPS for 48 h after pretreatment with OA at different concentrations. Pretreatment with OA was significantly effective in attenuating IL-6 and TNF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…10 We also demonstrated that administering these artificial lipoproteins to THP-1 macrophages and BV-2 microglial cells, OA can exert its pharmacological potential (specifically antioxidant and anti-inflammatory activities). 10,39 In the present investigation, we report, for the first time to the best of our knowledge, that physiological TRL assembled after ingestion of functional olive oil incorporate the administered OA. From Fig.…”
Section: Papermentioning
confidence: 48%
See 1 more Smart Citation
“…10 We also demonstrated that administering these artificial lipoproteins to THP-1 macrophages and BV-2 microglial cells, OA can exert its pharmacological potential (specifically antioxidant and anti-inflammatory activities). 10,39 In the present investigation, we report, for the first time to the best of our knowledge, that physiological TRL assembled after ingestion of functional olive oil incorporate the administered OA. From Fig.…”
Section: Papermentioning
confidence: 48%
“…10 We also demonstrated that administering these artificial lipoproteins to THP-1 macrophages and BV-2 microglial cells, OA can exert its pharmacological potential (specifically antioxidant and anti-inflammatory activities). 10,39…”
Section: Discussionmentioning
confidence: 99%
“…12,32 These effects vary depending on the fatty acid composition of the TRL, as those derived from olive oil-rich diets being less inflammatory than diets high in saturated fats. 33,34 Thus, in our study, particles triggered a molecular response that could be explained by different TRL components. The time-differential expression patterns we observed remain to be studied considering the physiological roles of the fatty acids, lipids and other components present in the TRL.…”
Section: G U R Ementioning
confidence: 55%
“…In a previous work, 32 we demonstrated that OA, a natural component of POO, modulated the inflammatory response in LPS-activated BV-2 cells, reducing in a dose-dependent manner the IL-1β, IL-6 and TNF-α production. Additionally, in other earlier research studies, 52 we treated THP-1 macrophages with human postprandial TRLs obtained after the intake of an OA-enriched olive oil, and found that the treatment reduced the IL-6 production. More recently, we also observed a moderate reduction in the expression and release of IL-6 in BV-2 cells treated with lab-made OA-containing TRLs.…”
Section: Discussionmentioning
confidence: 69%